Gluten-Free Diet - Elli, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In the last few years, an increasing number of individuals have adopted a gluten free diet (GFD). A significant proportion of that includes patients affected by celiac disease (CD), who have to follow a strict GFD for medical purposes. However, a high number of individuals are currently following a GFD without medical counseling and without a specific diagnosis needing a gluten withdrawal from the diet. This is due to the frequently incorrect information diffused on the Internet and mass media on the topic of GFD. For these reasons, research on the GFD and its clinical use and biological effects is urgently needed.